Antibiotic Residue in Raw Milk Collected from Dairy Farms and Markets in Nepal - Pokharel, S; Sedhai, S; Thakur, R; Gautam, MN; Aryal, D; Upadhyaya, N (Nepalese Veterinary Journal, 2023)
Antibiotic residue in food has been a growing public health problem due to the increasing global threats of antimicrobial resistance. Animal products including milk and meats might also contain residues of antibiotics as administering antibiotics in animals to treat infection is a common practice. However, the level of the presence of residues are not frequently quantified in Nepal. The objective of this study is to estimate the level of residues in milk collected from dairy farms and markets. A total of 935 raw milk samples were collected from 14 districts of 5 provinces namely Koshi, Madhesh, Bagmati, Gandaki and Lumbini province. Samples were tested at the Veterinary Standards and Drug Regulatory Laboratory (VSDRL) from June 2021 to Dec 2022 first using Rapid Test Kit followed by Gentamicin ELISA Kit for quantification. The result showed antimicrobial residue was present in 1.6% of the milk samples (15/935). On further quantification with ELISA, only 4 samples (0.42%) were positive for Gentamicin antibiotic which were below the MRL level. Extensive research with larger sample size and national representative samples are needed to understand the exact scenario of antibiotic residue in milk.